Effect of weak acidity regulation on the n-butene oligomerization over the modified Ni-ZSM-5 catalysts - Xu, Xi; Liu, Guangbo; Gao, Yurou; Gu, Suning; Li, Jianqing; Zhu, Caixia; Wang, Hui; Wu, Jinhu (Research on chemical intermediates, 2025)
Precisely describing the role of acid sites in catalysts is the key to develop highly efficient olefin oligomerization catalysts. However, the fine studies on catalyst acidity, which retain one of the strong/weak acid sites and deeply divide it into different parts by type or location, are less reported. Here, we prepared a series of Ni-ZSM-5 catalysts with short b-axis direction and tailored the weak acid sites of the catalysts by covering the target acid sites, as directional subtraction method. The detailed characterization results indicate that while keeping the texture properties, topological structure, and morphology of the catalysts essentially unchanged, the acidity of the catalysts had been directionally adjusted. The n-butene oligomerization evaluation and in situ DRIFTS results show that the external L acid sites and the B acid sites in the pore channel are identified as the crucial active sites for the n-butene oligomerization, for the Ni-ZSM-5 catalyst only with weak acid sites. The oligomerization capabilities of different weak acid sites are as follows: external L acid sites > the B acid sites in the pore channel > L acid sites in the pore channel. The L acid sites in the pore channel only exhibit isomerization activity. This work offers a new perspective for studying the role of different acid sites in olefin oligomerization catalysts and provides a new research strategy for the design of acidic catalysts.